Assessment of clinical trial participant patient satisfaction: a call to action. Issue 1 (December 2016) - Pflugeisen, Bethann; Rebar, Stacie; Reedy, Anne; Pierce, Roslyn; Amoroso, Paul
Abstract Background As patient satisfaction scores become increasingly relevant in today's health care market, we sought to evaluate satisfaction of the unique subset of patients enrolling in clinical trials in a research facility embedded within a community hospital system. Methods We developed and deployed a patient satisfaction survey tailored to clinical trial patients who consented to and/or completed a clinical trial in our research institute in the prior year. The survey was distributed to 222 patients. Likert scale responses were analyzed using top box and percentile rank procedures. Correlation analysis was used to evaluate associations between the clinical trial experience and intent to return to our system for routine care. Results Ninety surveys were returned in the 6 months following the mailing for a 41 % response rate; the bulk of these (N = 81) were returned within 6 weeks of the mailing. The questions with the highest ranking responses were related to interactions with staff (84th percentile or higher). Fifty-one point one percent of patients (64th percentile) strongly agreed that they would seek future care in our system. Patient intent to return to the provider seen during the clinical trial was most highly correlated with intent to seek future care within our system (r = 0.54, p < 0.0001). Reasons cited for clinical trial enrollment were generally altruistic. Conclusions Querying this special patient population is feasible and yields valuable insight into their experience with healthcare system-based clinical trials and the relationship between clinical trial participation and perception of the healthcare system as a desirable resource for routine medical care. We argue that this work is invaluable to the research community and submit a call to action to our peers to begin systematic evaluation of clinical trial patient satisfaction.